Mechanical Properties and the Morphology of Polypropylene Containing Di-p-methylbenzylidene - HAO, WENTAO; YANG, WEN (Asian Journal of Chemistry, 2010)
Mechanical properties and morphology of polypropylene (PP) containing di-p-methylbenzylidene (Me-DBS), a clarifying nucleating agent, were studied. In this studies, PP containing normal nucleating agent, sodium benzoate (SB), were used as comparison. It was found that the mechanical properties of PP with Me-DBS and SB were much different. Such differences should be contributed to the different nucleating mechanisms and different morphology of PP containing different nucleating agents.